2015
DOI: 10.1097/sap.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Hemangiomas Exhibit Neural Crest and Pericyte Markers

Abstract: Infantile hemangiomas (IHs) are the most common benign tumors of infancy and occur with greater than 60% prevalence on the head and neck. Despite their prevalence, little is known about the pathogenesis of this disease. Given the predilection of hemangioma incidence on the face and its nonrandom distribution on embryological fusion plates, we postulated that IHs are derived from pericytes of the neural crest. We performed an analysis on 15 specimens at various stages of the IH progression. Experiments performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…We concur with a number of their findings, including the expression of neural crest, δ-like kinase (DLK, also known as preadipocyte factor 1) and a number of embryonic stem cell markers within IH. However, unlike Spock et al, 1 we have demonstrated the expression of neural crest markers (p75, SOX-9, and Sox-10) on the endothelium of the microvessels, rather than the perivascular cells, of proliferating IH. 2 Furthermore, we have shown that the expression of DLK is localized to the same endothelium of proliferating IH, decreasing as the lesion involutes, 3 consistent with the report of Ritter et al 4 We have reported expression of the embryonic stem cell markers OCT-4, SSEA-4, and Nanog within IH, 5 with SSEA-4 and OCT-4 localizing to the endothelium (Fig.…”
contrasting
confidence: 95%
See 1 more Smart Citation
“…We concur with a number of their findings, including the expression of neural crest, δ-like kinase (DLK, also known as preadipocyte factor 1) and a number of embryonic stem cell markers within IH. However, unlike Spock et al, 1 we have demonstrated the expression of neural crest markers (p75, SOX-9, and Sox-10) on the endothelium of the microvessels, rather than the perivascular cells, of proliferating IH. 2 Furthermore, we have shown that the expression of DLK is localized to the same endothelium of proliferating IH, decreasing as the lesion involutes, 3 consistent with the report of Ritter et al 4 We have reported expression of the embryonic stem cell markers OCT-4, SSEA-4, and Nanog within IH, 5 with SSEA-4 and OCT-4 localizing to the endothelium (Fig.…”
contrasting
confidence: 95%
“…Based on our previous findings of the expression of primitive mesoderm on the endothelium of proliferating IH, 2 1 However, to better understand the article in real depth, we kindly wished to raise two questions.…”
mentioning
confidence: 99%
“…Recent data have implicated IH as an embryonic developmental anomaly due to aberrant proliferation and differentiation of a hemogenic endothelium (6) derived from a primitive mesoderm with a neural crest phenotype (7, 8). There is also evidence of a crucial role for the endocrine renin–angiotensin system (RAS) with the vasoactive peptide, angiotensin II (ATII), as a key regulator of this hemogenic endothelium (911).…”
Section: Introductionmentioning
confidence: 99%
“…Microscopically, sarcomas and hemangiomas have a significant difference in appearance. While sarcomas are mainly composed of spindle cells [6], hemangiomas have lobular vascular proliferation and an appearance of microvessels [12]. Sarcomas tend to have more aggressive behavior and worse prognosis despite extensive resections and adjuvant therapy [2,3,6], and they do not respond to β-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…Hemangiomas are considered the most common benign tumor in children, usually involving the skin of the face and neck [11][12][13]. Intracranial involvement of hemangiomas is rare and usually appears along with cutaneous lesion [5,13].…”
Section: Introductionmentioning
confidence: 99%